Genetic association of mosaic loss of chromosome Y with prostate cancer in men of European and East Asian ancestries: a Mendelian randomization study - Kobayashi, Takuro; Hachiya, Tsuyoshi; Ikehata, Yoshihiro; Horie, Shigeo (Frontiers in Aging, 2023)
Background: Genomic instability is a significant hallmark of aging and has a major impact on aging biology. Mosaic loss of chromosome Y (mLOY) in blood cells is a common chromosomal abnormality in aging men and is considered an indicator of genomic instability. Previous studies have indicated a connection between mLOY and prostate cancer risk, but the causal relationship has not been fully established. Methods: To determine the causal effect of mLOY on prostate cancer, we conducted a Mendelian Randomization (MR) study in two ancestral groups. We utilized 125 and 42 mLOY-associated variants as instrumental variables (IVs) in European and East Asian GWAS of prostate cancer, respectively. Summary-level data on prostate cancer was obtained from the PRACTICAL consortium (79,148 cases and 61,106 controls of European ancestry) and the Biobank Japan consortium (5,408 cases and 103,939 controls of East Asian ancestry). A single population was used to assess the causal relationship in East Asian ancestry. Our main method for obtaining MR results was inverse-variance weighting (IVW), and we conducted sensitivity analyses to confirm the robustness of our results. Finally, we combined the estimates from both sources using a fixed-effects meta-analysis. Results: Our MR analysis using the IVW method showed that a one-unit increase in genetically predicted mLOY was associated with an increased risk of prostate cancer in the PRACTICAL consortium (OR = 1.09, 95% CI: 1.05-1.13, P = 1.2 × 10-5), but not in the Biobank Japan consortium (OR = 1.13, 95% CI: 0.88-1.45, P = 0.34). Sensitivity analyses robustly indicated increased odds ratios for prostate cancer with every one-unit increase in genetically predicted mLOY for the PRACTICAL consortium. Furthermore, mLOY was found to be associated with prostate cancer risk in a meta-analysis of both sources (OR = 1.09, 95% CI: 1.05-1.13, P = 8.0 × 10-6). Conclusion: Our MR study provides strong evidence that higher mLOY increases the risk of prostate cancer. Preventing mLOY may be a means of reducing the risk of developing prostate cancer.